Cost Efficiency of Dairy Farming in New Zealand: A Stochastic Frontier Analysis. (December 2014) - Jiang, Nan; Sharp, Basil
Abstract : Research on the efficiency of dairy farming in New Zealand is limited and has focused predominantly on technical efficiency. We contribute to the literature on empirical analysis by examining cost efficiency of New Zealand dairy farms. We construct simplified translog stochastic cost frontiers based on an unbalanced panel of 824 farms. Average cost efficiency is estimated at 83 percent for dairy farms in the North Island and 80 percent for farms in the South Island. Our analysis of the relationship between inefficiency and farm characteristics suggests significant associations between cost efficiency and capital intensity, livestock quality, and farm size.